2017
DOI: 10.1159/000477485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Inducible VEGF Expression and Tumor Progression in a Breast Cancer Model

Abstract: Background: Tumor derived vascular endothelial growth factor (VEGF) can stimulate proliferation and migration of endothelial cells and recruit endothelial progenitor cells into tumors for vascular formation via a paracrine manner. Now increasing evidence suggests that VEGF also serves as an autocrine factor promoting cell survival and tumor angiogenesis. Real time visualization of VEGF activity in the early stages of tumor formation using molecular imaging will provide unprecedented insight into the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…HAECs were stimulated with LIPUS in the presence or absence of H 2 O 2 . The cells remaining on the membrane facing the upper chamber were rubbed away, and the cells that had migrated onto the reverse side of the membrane were fixed with 4% paraformaldehyde and stained with 0.1% crystal violet [23]. …”
Section: Methodsmentioning
confidence: 99%
“…HAECs were stimulated with LIPUS in the presence or absence of H 2 O 2 . The cells remaining on the membrane facing the upper chamber were rubbed away, and the cells that had migrated onto the reverse side of the membrane were fixed with 4% paraformaldehyde and stained with 0.1% crystal violet [23]. …”
Section: Methodsmentioning
confidence: 99%
“…At the heart of this signaling network are vascular endothelial growth factors (VEGFs). VEGFs play an important role in promoting angiogenesis and maintaining the integrity of endothelium [5, 6]. VEGF production and signaling are partly dependent on the induction of hypoxia inducible factor-1 alpha (HIF-1α) expression by mechanistic target of rapamycin (mTOR) [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor growth and metastasis are dependent on the degree of neovascularization, which is regulated by pro-angiogenic and anti-angiogenic factors. Vascular endothelial growth factor (VEGF) is an important angiogenic factor and has been studied most extensively in a number of types of cancer, including breast cancer and renal cell carcinoma (7,8). Previous studies have demonstrated that VEGF stimulation may increase Livin expression and induce the pathogenesis of human esophageal carcinoma and cervical cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%